Can media campaign messages influence change towards ecologically based rodent management? - Flor, Rica Joy B.; Singleton, Grant R. (Commonwealth Scientific and Industrial Research Organisation, 2011)
Context In Asia, losses to rodents contribute to the undernourishment of smallholder families. Ecologically based rodent management (EBRM) has become the national policy for rodent management in rice-based agriculture in Indonesia, the Philippines and Vietnam. EBRM requires community action. Therefore we need to develop communication campaigns that increase community involvement in rodent management. Aims This study evaluates the effects of a campaign to promote EBRM in a community that suffers chronic rodent losses to their rice crop. We hypothesised that the campaign would create changes in rodent management by farmers based on key messages delivered. Methods We documented existing beliefs and management practices, and captured changes in knowledge, attitudes and behaviour of smallholder farmers after the campaign. We also document benefits to the community. We used qualitative tools to evaluate existing beliefs and management practices of rodents in nine villages in Zaragosa, one of which was a focus village for the campaign. Key results Farmers who were influenced by the campaign had significantly higher mean rank scores in knowledge and attitudes pertaining to key messages of the campaign, such as working together, proper timing of management actions, and that rodents can be controlled. Farmers who heard the campaign obtained yields that were higher by 0.7 t ha–1 compared with those with no exposure to the campaign. A year after the campaign, the increase in rice yield in Zaragosa was sufficient to feed 1375 adult Filipinos for a year. The campaign influenced policy on rodent management in Zaragosa and subsequently at the provincial level. Conclusions A media campaign with support from local leaders and extension staff is an effective way to disseminate EBRM, leading to positive economic benefits for smallholder farmers. A media campaign alone is less effective. Implications A communication campaign on EBRM with follow-up support from extension experts is a highly effective pathway for changing attitudes and practices of smallholder farmers on rodent management, and for effective dissemination of EBRM.